Social insertion in adolescents: A socio-psychological study - Herrera, Dora (2002)
This research is aimed to determine the socio-psychological correlates of Social Insertion in adolescents who has finished secondary education. The research model considers predictor, mediator and criterion (Social Insertion) variables assessed in a correlational and longitudinal study. The results show changes in the Social Insertion level according to the socio-economic level. In terms of School Culture it has been found that adolescents perceive that their schools orient them to Social Insertion under the following hierarchy: first, to pursue university education; second, to follow technical studies; third, to find employment and fourth, to form a family. Another finding is the existence of a positive association between the Social Insertion levels and Parents’ expectations. Further results indicate that the Future Time Perspective is different as a function of the socio-economic level.